Reflective Teaching Approach: Theory And Practice For Effective Arabic Learning/ Pendekatan Reflective Teaching: Teori Dan Praktik Untuk Pembelajaran Bahasa Arab Yang Efektif - Faiq Ilham Rosyadi; Hisyam Zaini; Nasiruddin Nasiruddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The approach to learning Arabic often applied is only limited to a specific focus. This causes the quality of learning Arabic not to reach its maximum rate. This study aims to formulate the Arabic language learning approach framework through reflective thinking. This article is from a literature study using the descriptive analysis method. The data collection technique used in this research is through exploration and in-depth study of documents, books, journal articles, or other text sources related to the research subject. The primary data of this research is the educational framework